Handbook of research on modernization and accountability in public sector management - Azevedo, Graça Maria do Carmo (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2018)
"This book disseminates methodologies that would allow public institutions to implement practices, consistent with values of ethics, rigor, transparency and accountability to promote accountable public sector managers and discusses the processes of control and risk management and stress their importance for the reliability of financial reporting"